Hubungan Penggunaan Obat Antihipertensi Dengan Angka Kejadian Penyakit Parkinson Di RSUD Dr Moewardi Surakarta - LESTARI, Astri Andra Sari Yunita (2015)
which can influence the part of our brain that called as ganglia basalis when the level of dopamine was declined the characterized such as rest tremor, rigidity, and bradykinesia. Parkinson's disease has a variety of risk factors one of them is the using of antihypertensive drugs. Purpose of study: The purpose of this study is to know the relationship between the using of antihypertensive drug and the incidence of Parkinson's disease in DR Moewardi Hospital, Surakarta. Research method: The research method of this study is using the design of analytic observational with case-control approach. The research was done on 2 to 20 March 2015 in the unit of medical record DR Moewardi Hospital, Surakarta. The samples of this study were 30 patients with Parkinson's disease and not accordance with the restriction criteria, using purposive sampling technique. The technique of analyzing data is using Chi-square with SPSS 17 for Windows. Result of Study: The distribution of 60 respondents obtained 16 men and 14 women with a range of 66 until 75 years old. The Parkinson's patients that using antihypertensive drug are 17 patients and the patients not using antihypertensive drug are 13 patients. The result of Chi-square analysis shows the significance value as 0,037 (p<0,05). Conclusion of Study: There are found the relationship between the using of antihypertensive drug and the incidence of Parkinson's disease in DR Moewardi Hospital, Surakarta (p<0,05).